Calendar Effect in the Malaysia Stock Market - Hue, Han Pin (2010)
The presence of the calendar effect has been recognized in equity markets throughout the world. Most of the studies reporting on this pattern have relied on the Ordinary Least Square (OLS) methodology. More recently, researchers have improved their studies by using a more advance methodology, producing more robust results. This paper is to examine the existence of calendar effect in the Malaysia stock market by using the OLS as well as Generalized Autoregressive Conditionally Heteroskedastic (GARCH) models. To examine the daily and monthly calendar anomalies in the Kuala Lumpur Composite Index (KLCI), from the period of 1993 to 2005 by categorizing it into three periods, pre-crisis, during crisis and post crisis period. The results indicate that month of the year effect does not exist in Malaysia as a calendar anomaly while day-of-the week effect does. These findings are consistent with the previous studies, of which they had found a negative mean return on Monday. Besides, further analysis is carried out by using TGARCH and EGARCH model to capture the asymmetrical behavior of investors. Finally yet importantly, this study also looks into the time zone hypothesis, of which it attempts to find out if the US return on day t (effectively day t-1 for Malaysian investors) will have an impact on Today’s Malaysia return. And, based on the findings, can conclude that US return does pose an impact on Malaysia return, resulting in a seasonal pattern in the market returns.